2022
DOI: 10.1002/mame.202200419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Fusion Quality of Bead Foams Made from Polybutylene Terephthalate (E‐PBT) Depending on the Processing Temperature

Abstract: Increasing requirements are leading to new developments in bead foam materials. Engineering thermoplastics such as polybutylene terephthalate (PBT) outperform standard bead foams in thermal stability. In order to obtain molded parts, beads are fused together using steam chest molding. Classical theories for the fusion mechanism, explaining the molding of amorphous EPS (expandable polystyrene) or semi‐crystalline EPP (expanded polypropylene), cannot be applied to E‐PBT (expanded polybutylene terephthalate). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The different observations regarding the bead fusion potentials can be explained with the help of the previously carried out investigations for single beads (DSC, OCC, TMA, DMTA). Similar correlations have already been identified in previous studies . The comparison between the single beads showed that E-PBT Pocan 1100, 1300, and 1400 had the highest OCC (Figure ) and therefore the highest shrinkage (Figure ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The different observations regarding the bead fusion potentials can be explained with the help of the previously carried out investigations for single beads (DSC, OCC, TMA, DMTA). Similar correlations have already been identified in previous studies . The comparison between the single beads showed that E-PBT Pocan 1100, 1300, and 1400 had the highest OCC (Figure ) and therefore the highest shrinkage (Figure ).…”
Section: Resultssupporting
confidence: 88%
“…Similar correlations have already been identified in previous studies. 50 The comparison between the single beads showed that E-PBT Pocan 1100, 1300, and 1400 had the highest OCC (Figure 10) and therefore the highest shrinkage (Figure 12). Due to the shrinkage, there is no sufficient contact surface between the beads in the cavity during the steam chest molding process, so that no fusion can be realized for these beads.…”
Section: Optical Appearance and Cell Morphologymentioning
confidence: 98%
“…Viscosity also has a significant effect on foam morphology, as already shown in earlier works. [11,15,48] The bead foams were produced as described in our previous study via a tandem foam extrusion line coupled on an underwater granulator using CO 2 as a blowing agent. [11] The influence of molecular weight and varied viscosity based on different chain architectures on foam density, cell density, and morphology was investigated.…”
Section: Change In Viscosity and Foam Structuresmentioning
confidence: 99%
“…The current state-of-the-art approach is the use of chemical modifications to overcome those issues, as it was shown in previous works. [11,15] Hence, the melt modification with CE during reactive extrusion processes is a promising approach to increase the molecular weight (branching and/or crosslinking) and consequently to change the rheological properties (i.e., increased shear viscosity and melt strength). [3,[16][17][18] Chain extenders are multifunctional additives that can react with the terminal functional groups of the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…This was because using autoclave foaming technology, the polymer matrix foamed in a solid state, which was beneficial to obtain a cellular structure with a high closed cell content and post-molding. 36 However, this bead foam preparation process includes complex procedures, such as premixing, pelletizing, dryness, gas saturation, foaming, and so forth, which requires a longer time and higher costs. Different from EPLA-#0, the optical morphology and the cellular structures of ExPLA-#1 were bare (Figures 3b 1 and 4b-b 2 ) because it cut from foamed strips with a fixed morphology.…”
Section: Foaming Behavior and Morphologies Of Various Pla Bead Foamsmentioning
confidence: 99%